NEW METHODS OF TREATMENT OF BRAIN AND SPINAL CORD TUMORS - Tukhtanboev Ibrokhimjon (European Science Publishing, 2025)
The treatment of brain and spinal cord tumors has evolved significantly in recent years, driven by advancements in surgical techniques, radiotherapy, drug delivery systems, and immunotherapy. Surgical innovations, including minimally invasive procedures, intraoperative imaging, and functional mapping, have improved the precision of tumor resection, minimizing neurological deficits and enhancing patient outcomes. In parallel, advancements in radiotherapy, such as proton beam therapy and stereotactic radiosurgery, allow for more targeted radiation delivery, reducing collateral damage to surrounding healthy tissue.
Keywords: Brain tumors, spinal cord tumors, neurosurgery, minimally invasive surgery, targeted therapy, immunotherapy, gene therapy, chemotherapy, precision medicine, radiotherapy, proton beam therapy, stereotactic radiosurgery, nanoparticle drug delivery, blood-brain barrier, convection-enhanced delivery, small molecule inhibitors, molecular profiling, genetic sequencing